224 VALIDATION OF TRIAXIAL ACCELEROMETER AND PHYSICAL ACTIVITY MONITORING IN CHILDREN. (1st January 2006) - Liu, W. Y.; Lee, M.; Rodriguez, S.; Chang, R. -K.
Abstract : Background: Accelerometers are used to objectively measure the physical activity of adults. Data on the use of accelerometers in children have been limited. Purpose: To validate a triaxial accelerometer in physical activity measurement in children and to use accelerometers to monitor daily activity level of healthy children in their natural environment. Methods: For accelerometer validation, 10 subjects (ages 9-16) performed a treadmill test using the Bruce Protocol. Activity count (counts per minute or cpm), oxygen consumption (VO2 ) values were collected and metabolic equivalent (MET) values were calculated. For physical activity monitoring, 14 healthy children (ages 8-14) wore an accelerometer 24 hours per day for 7 consecutive days to track minute-by-minute physical activity level. For each subject, three complete (24 hours) weekdays and two weekend days were selected for analysis. Results: In accelerometer validation, we found strong correlation between activity counts and physical exertion by METs ( r = .97, p = .001). Moderate activity level of 8 METs is equivalent to an activity count of 2, 000 cpm. In activity monitoring, the mean age was 11 years. Overall activity was 327 ± 24 cpm. Day time activity was 510 ± 32 cpm. Nighttime activity was 13 ± 2 cpm. The subjects were more active during the weekday than weekend (372 ± 30 cpm vs 291 ± 27 cpm, p = .04). Conclusions: Accelerometry is a valid objective measure of children's physical activity.